Twórczość komediowa Mieczysława Fijałkowskiego - Mazurek, Jerzy (Zeszyty Wiejskie, 2016)
Mieczysław Fijałkowski (1888–1972) was an author of 12 comedies, three volumes of short stories and also memoires. The memoirs, as well as some of the short stories, were published; alas, none of his plays was. Nevertheless, in the interwar period they won a considerable popularity and were put on stage by a significant number of famous artists and directors. They were staged also after the Second World War, not in Warsaw, however, but rather in the provinces. The works by Fijałkowski are all the more interesting because of the fact that he was not a professional writer. For 50 years he was working in agriculture as agronomist, thus the country is the main theme of his artistic output. It is a testimony of social transformation that took place in Poland in the 20th century.